2018
DOI: 10.1088/1758-5090/aaf3c9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of perfusable 3D hepatic lobule-like constructs through assembly of multiple cell type laden hydrogel microstructures

Abstract: The in vitro reproduction of three-dimensional (3D) cellular constructs to physiologically mimic human liver is highly desired for drug screening and clinical research. However, the fabrication of a liver-mimetic 3D model using traditional bottom-up technologies is challenging owing to the complex architecture and specific functions of real liver tissue. This work proposes a versatile strategy for spatially assembling gear-like microstructures encapsulating multiple cell types, and reorganizing them into 3D lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 59 publications
2
47
0
Order By: Relevance
“…These results demonstrated that co-culture of HepG2 cells with NIH/3T3 cells in the 3D microtissues enhanced albumin secretion and urea synthesis than mono-culture of HepG2 cells in the 3D microtissues. Moreover, during the culture period, the albumin secretion and urea synthesis of the co-cultured 3D microtissues maintained higher level than that of the PEGDA-based 3D constructs in our previous work [20]. The PEGDA-based precursor solution is thicker than the GelMA one, which means cells undergo a harsh environment during the process for fabricating cellular PEGDA micromodules, thus may cause cells injury and influence cell recovery and function expression.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…These results demonstrated that co-culture of HepG2 cells with NIH/3T3 cells in the 3D microtissues enhanced albumin secretion and urea synthesis than mono-culture of HepG2 cells in the 3D microtissues. Moreover, during the culture period, the albumin secretion and urea synthesis of the co-cultured 3D microtissues maintained higher level than that of the PEGDA-based 3D constructs in our previous work [20]. The PEGDA-based precursor solution is thicker than the GelMA one, which means cells undergo a harsh environment during the process for fabricating cellular PEGDA micromodules, thus may cause cells injury and influence cell recovery and function expression.…”
Section: Resultsmentioning
confidence: 87%
“…However, these studies are focused on cellular sheets constructions with simple structures, which could not mimic complex 3D tissue architectures at micro scale. In our previous study, poly(ethylene glycol) diacrylate (PEGDA) hydrogel was used to fabricate 3D constructs encapsulating hepatocytes and fibroblasts to mimic liver lobules [20]. PEGDA hydrogel has strong mechanical properties for 3D assembly, but it is non-biodegradable which limits cell organization for 3D.…”
Section: Introductionmentioning
confidence: 99%
“…For example, microstructures can be moved, rotated, and patterned by a bubble‐actuated microrobot in 2D, or by multiple light‐controlled surface bubble robots . To assemble 3D constructs, hydrodynamic forces are introduced by the floating bubble, which is then injected by a glass capillary under the cell‐laden microstructures . At the same time, a glass rod can be employed as a holder for collecting annular microcomponents, resulting in the formation of a vascular‐like microtube.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, PEGDA was modified by Arg-Gly-Asp-Ser (RGDs) to improve cell adhesion and viability. The specific procedure was introduced in References [32,33]. The fabrication of micromodules is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%